EMMPRIN in extracellular vesicles from peritoneal mesothelial cells stimulates the invasion activity of diffuse-type gastric cancer cells - Sugimoto, Atsushi; Okuno, Tomohisa; Miki, Yuichiro; Tsujio, Gen; Sera, Tomohiro; Yamamoto, Yurie; Kushiyama, Shuhei; Nishimura, Sadaaki; Kuroda, Kenji; Togano, Shingo; Maruo, Koji; Kasashima, Hiroaki; et al. (Cancer letters, 2021)
Peritoneal metastasis of gastric cancer (GC) results in extremely poor prognoses. The peritoneal cavity is covered by a monolayer of peritoneal mesothelial cells (PMCs). Interactions between GC cells and PMCs might play a pivotal role in peritoneal metastasis. Extracellular vesicles (EVs) correlate with intercellular communication. Although intercellular communication between cancer cells and PMCs might be associated with the peritoneal metastatic process, the role of EVs from PMCs remains unclear. We investigated the effects of EVs from PMCs on GC cells. Three GC cell lines (OCUM-12, NUGC-3, and MKN74) and four mesothelial cell lines were used. The effects of EVs derived from the PMCs on the invasion and migration of GC cells were evaluated by Matrigel invasion assay. Factors contained in the PMC EVs were analyzed; extra-cellular matrix metalloproteinase inducer (EMMPRIN) was detected in the EVs. The effects of an EMMPRIN inhibitor on the invasion-stimulating activity of EVs were examined. The EMMPRIN expressions of 110 GCs were evaluated by immunohistochemistry. PMC EVs significantly promoted the invasion of diffuse-type GC cells, i.e., OCUM-12 and NUGC-3 cells. EMMPRIN in the EVs stimulated the invasion of OCUM-12 and NUGC-3 cells. The invasion-stimulating activity of PMC EVs was inhibited by the EMMPRIN inhibitor. A high EMMPRIN expression in PMCs was significantly associated with worse cancer-specific survival and peritoneal-recurrence-free survival. EMMPRIN in EVs from PMCs might stimulate the malignant progression of diffuse-type GC. EMMPRIN might be a useful prognostic marker of recurrence in GC patients. •Peritoneal mesothelial cell (PMC) extracellular vesicles (EVs) contains EMMPRIN.•EMMPRIN in EVs promotes the invasion of diffuse-type gastric cancer (GC) cells.•EMMPRIN in PMC EVs might be a novel therapeutic target in diffuse-type GC.